Commitment and Replacement of Existing SaaS-Delivered Applications: A Mixed-Methods Investigation - Xiao, Xiao; Sarker, Saonee; Wright, Ryan T.; Sarker, Suprateek; Mariadoss, Babu John (MIS Quarterly, 2020)
As the highest level of cloud computing delivery model, Software-as-a-Service (SaaS) has gained considerable popularity in the industry as a new way of deploying IT solutions, due to its low cost and high elasticity. However, the new business model associated with SaaS highlights the importance for SaaS vendors to understand how to retain customers in a hyper-competitive market. In particular, increasing customer retention and preventing customers from replacing the adopted SaaS applications has become a crucial task for all SaaS vendors. In this study, using a mixed-methods approach, and drawing on the cognitive–affective–conative– action (CACA) framework, we investigate the IS replacement phenomenon in the context of SaaS-delivered applications. Our qualitative study allows us to develop an IS-centric view of customer commitment by differentiating between organizations’ commitment to the SaaS application and to the cloud computing technology in general, while the subsequent quantitative study validates the difference between the two types of commitment and helps understand how they together influence organizations’ intentions to replace a SaaS application. Our results generate important theoretical implications for research on IS replacement and clarifies the concept of customer commitment. We also offer practical guidelines to SaaS vendors on how to retain customers so as to survive/thrive in this competitive market.